Integrasi Micro Habit Islami dalam Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Konsistensi Akhlak Siswa di Sekolah MA al-Amin - Mendy Harmoko; Ani Ulfiana; Aisatun Nafisa (ALSYS, 2026)
Students’ low consistency in morals in daily life, despite having received Islamic Religious Education (PAI) instruction, indicates the need for a more applicable and sustainable character-building strategy. This study aims to analyze the integration of Islamic micro-habits in PAI learning to improve students’ moral consistency at MA Al-Amin. This study used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the integration of Islamic micro-habits was carried out through routine habituation, teacher role modeling, reinforcement, and continuous supervision. This strategy was proven to improve students’ discipline, responsibility, and respectful attitudes. The conclusion of this study emphasizes that Islamic micro-habits are effective in sustainably shaping students’ moral consistency. The implications of this study indicate that small habits practiced consistently can be applied as a practical approach to strengthening character education in schools.